Postoperative Infection in Arthroscopic ACL Reconstruction Using Hamstring Autograft - Abbas Khan, Akhtar Hussain, Ahmad Zeb, Yasir Mehmood, Farmanullah, Zain Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Because of the increasing number of participants in sports activities and traffic accidents, the frequency of anterior cruciate ligament (ACL) injuries has been increasing. Arthroscopic ACL reconstruction, which is widely used in the treatment of complete ACL tears, is an effective method for preventing chronic instability and early degenerative arthritis. Objective: To determine the postoperative infection in arthroscopic ACL reconstruction using hamstring autograft Methodology: This study was retrospective study carried out at the department of orthopaedics, Afridi Teaching Hospital, Peshawar for a period of six months from February 2022 to July 2022. The postoperative infection status of all the included patients was taken from the hospital record. IBM SPSS version 23 was used to conduct all statistical analyses. Results: In the current study, a total of 60 patients were included. There were 51 (85%) males and 9 (15%) females in our study. Based on the rate of infection amongst 60 patients the frequency of infection was 2 (3.33%). Conclusion: Infection after arthroscopic ACL reconstruction using hamstring autograft is a relatively infrequent but devastating complication for patients. Better knowledge of the proper treatment protocols will contribute to improved quality of care for patients. Keywords: Postoperative infection; arthroscopic ACL reconstruction; hamstring autograft